The Influence of Motivation on Cultural Tourism in Kampung Batik Laweyan - Septian; Wisnu Untoro (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Kampung Batik Laweyan in Surakarta is one of the oldest batik centers in Indonesia, which has developed since the 16th century during the Pajang Kingdom. The peak of Laweyan's glory occurred in the early 20th century until around 1970, when this area became the largest batik production and trade center in Solo. However, since around 1970, Laweyan's glory began to decline. The entry of printed batik and batik-patterned textiles produced in bulk, especially from abroad, caused written batik and Laweyan stamps to lose competition in terms of price and production volume. The process of making traditional batik that takes a long time is not able to match the efficiency of modern industry. As a result, many batik businesses in Laweyan went out of business, the next generation was reluctant to continue the family business, and batik making activities in this village stagnated for almost three decades. The decline marks the end of Laweyan's glory era as the center of the pure batik industry, as well as a turning point for the transformation of Laweyan in the next era as a batik village based on cultural heritage and tourism. This study aims to examine the influence of motivation on various aspects of cultural tourism experience in Kampung Batik Laweyan, with a focus on tourists from the general public. With a quantitative approach through a questionnaire survey based on a 5-point Likert scale, this study involved visitors over 18 years old who were selected by purposive sampling technique. The variables tested included authenticity/authenticity, education, entertainment, hedonism, customer engagement, customer satisfaction, and motivation. The analysis was carried out using regression and mediation tests to test the relationship between variables. The results of the research are expected to enrich the literature of cultural tourism and provide practical recommendations in improving the experience and satisfaction of visitors to Kampung Batik Laweyan.